Impact of Crystal Types of AgFeO2 Nanoparticles on the Peroxymonosulfate Activation in the Water - Zhao, Ying; An, Hongze; Feng, Jing; Ren, Yueming; Ma, Jun (Environmental science & technology, 2019)
A simple co-precipitation method was developed to synthesize AgFeO2 nanoparticles (NPs) with hexagonal 2H and 3R polytypes coexistence. The ratio of 2H and 3R types in AgFeO2 NPs were regulated by controlling the calcination temperature (300, 400, and 500 °C). Such AgFeO2 NPs were used as heterogeneous catalysts to activate peroxymonosulfate (PMS) for the removal of Orange I (OI) in the water. External water conditions effects and the stability of AgFeO2 NPs were investigated. The catalytic performance of AgFeO2 NPs was found to be significantly enhanced with the increasing content of 2H-AgFeO2. 1O2, O2 •–, SO4 •–, and •OH were identified as the dominating reactive oxygen species (ROSs) participated in the catalytic process. The electron transfer of Ag0/Ag+ and Fe2+/Fe3+ cycles facilitated the decomposition of PMS to generate ROSs. The surface hydroxyl groups (−OH) were regarded as the catalytic active sites. The higher 2H-AgFeO2 content in AgFeO2 NPs promoted the concentration of surface hydroxyl groups (C –OH) and the reactivity of AgFeO2 NPs for PMS activation. Based on theoretical calculations, the 2H-AgFeO2 (004) plane with more Fe sites was more conducive to binding with the −OH compared to the 3R-AgFeO2 (012) plane, ascribed to the stronger adsorption energy and shorter Fe–O bond length between 2H-AgFeO2 and −OH.